Research-Relevant Background Lesions and Conditions in Common Avian and Aquatic Species. (30th March 2021) - Mangus, Lisa M; França, Monique S; Shivaprasad, H L; Wolf, Jeffrey C
Abstract: Non-mammalian vertebrates including birds, fish, and amphibians have a long history of contributing to ground-breaking scientific discoveries. Because these species offer several experimental advantages over higher vertebrates and share extensive anatomic and genetic homology with their mammalian counterparts, they remain popular animal models in a variety of fields such as developmental biology, physiology, toxicology, drug discovery, immunology, toxicology, and infectious disease. As with all animal models, familiarity with the anatomy, physiology, and spontaneous diseases of these species is necessary for ensuring animal welfare, as well as accurate interpretation and reporting of study findings. Working with avian and aquatic species can be especially challenging in this respect due to their rich diversity and array of unique adaptations. Here, we provide an overview of the research-relevant anatomic features, non-infectious conditions, and infectious diseases that impact research colonies of birds and aquatic animals, including fish and Xenopus species.